Use of aromatherapy and auriculotherapy in elderly participants in a Physical Activity group (Research, Society and Development, 2022)
In Brazil, health care has been gaining new care practices in order to bring greater integrality to individuals, as well as meeting the expanded concept of health-disease-care. The use of Integrative and Complementary Practices in Health (PICs) is pointed out as an important intervention for the consolidation of positive perspectives in this process. The objective of this work is to report the experience of using aromatherapy and auriculotherapy in elderly people participating in a physical activity group within the scope of primary care, referring to the actions developed by the Physical Education category of the Multiprofessional Residency program in Family and Community Health at the University State of Piauí, from July to November 2021, targeting elderly people participating in a group called Actively. For the collection of information, the following were used: participant observation and records of actions in a logbook after application of the PICs. Subsequently, the analysis of the information was carried out through the systematization and grouping of ideas in a critical and reflective way with the literature. Therefore, it was possible to verify that the construction of co-responsibility of care and new ways of doing health in the territory is capable of reducing the repressed demand in the continuity of care with the elderly population, providing spaces for health promotion and expanding the use of PICS to beyond institutional walls, Exposing the need, through the context experienced by the elderly, to give greater visibility to the application of these therapies as alternatives to non-drug treatment by health professionals, in the elderly population.